Low thermal expansion in conjunction with improved mechanical properties achieved in Mg-Gd solid solutions - Cuihong Wang; Zhihua Dong; Bin Jiang; Lei Wang; Zhiying Zheng; Ang Zhang; Jiangfeng Song; Dingfei Zhang; Levente Vitos (Materials & Design)
Addition of Gd with relatively large solubility is demonstrated to significantly reduce the coefficient of thermal expansion (CTE), while improving obviously the mechanical properties of Mg matrix. A good combination of low CTE, high strength and ductility is obtained at Gd content of ∼ 10.6 wt%. According to first-principle predictions for Mg-Gd solid solutions, the decreased CTE upon alloying with Gd is predominately determined by the reduction of lattice vibrational contribution. This reduction emerges basically from the weakened anharmonic effect, which is represented by the decreased Grüneisen parameter. The refined grain size and solution of Gd in bulk matrix predominate the increased strength of Mg-Gd alloys. The segregation of Gd at grain boundary is found to yield important impact on the refined grain size. Furthermore, while the obvious reduction of ductility at relatively high Gd contents is related to the precipitation of coarse Mg5Gd phase, the high ductility achieved at relatively low Gd contents is closely correlated with the activation of non-basal slips. It emerges fundamentally from the varied influence of Gd on the unstable stacking fault energy of basal and non-basal slips. The present advances enhance the understanding of designing innovative Mg alloys with tunable thermal expansion and mechanical properties.